Recruitment of racial/ethnic minority older adults through community sites for focus group discussions - Mary E. Northridge; Michele Shedlin; Eric W. Schrimshaw; Ivette Estrada; Leydis De La Cruz; Rogelina Peralta; Stacia Birdsall; Sara S. Metcalf; Bibhas Chakraborty; Carol Kunzel (BMC, 2017)
Abstract Background Despite a body of evidence on racial/ethnic minority enrollment and retention in research, literature specifically focused on recruiting racially/ethnically diverse older adults for social science studies is limited. There is a need for more rigorous research on methodological issues and the efficacy of recruitment methods. Cultural obstacles to recruitment of racial/ethnic minority older adults include language barriers, lack of cultural sensitivity of target communities on the part of researchers, and culturally inappropriate assessment tools. Methods Guided by the Consolidated Framework for Implementation Research (CFIR), this study critically appraised the recruitment of racial/ethnic minority older adults for focus groups. The initial approach involved using the physical and social infrastructure of the ElderSmile network, a community-based initiative to promote oral and general health and conduct health screenings in places where older adults gather, to recruit racial/ethnic minority adults for a social science component of an interdisciplinary initiative. The process involved planning a recruitment strategy, engaging the individuals involved in its implementation (opinion leaders in senior centers, program staff as implementation leaders, senior community-based colleagues as champions, and motivated center directors as change agents), executing the recruitment plan, and reflecting on the process of implementation. Results While the recruitment phase of the study was delayed by 6 months to allow for ongoing recruitment and filling of focus group slots, the flexibility of the recruitment plan, the expertise of the research team members, the perseverance of the recruitment staff, and the cultivation of change agents ultimately resulted in meeting the study targets for enrollment in terms of both numbers of focus group discussions (n = 24) and numbers of participants (n = 194). Conclusions This study adds to the literature in two important ways. First, we leveraged the social and physical infrastructure of an existing program to recruit participants through community sites where older adults gather. Second, we used the CFIR to guide the appraisal of the recruitment process, which underscored important considerations for both reaching and engaging this underserved population. This was especially true in terms of understanding the disparate roles of the individuals involved in implementing and facilitating the recruitment plan.